2009
DOI: 10.1164/rccm.200809-1435oc
|View full text |Cite
|
Sign up to set email alerts
|

Altered Upper Airway and Soft Tissue Structures in the New Zealand Obese Mouse

Abstract: Rationale: The effect of obesity on upper airway soft tissue structure and size was examined in the New Zealand Obese (NZO) mouse and in a control lean mouse, the New Zealand White (NZW). Objectives: We hypothesized that the NZO mouse has increased volume of neck fat and upper airway soft tissues and decreased pharyngeal airway caliber. Methods: Pharyngeal airway size, volume of the upper airway soft tissue structures, and distribution of fat in the neck and body were measured using magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 66 publications
(72 reference statements)
1
80
0
1
Order By: Relevance
“…Since obesity is a major risk factor for obstructive sleep apnea, the upper airway of obese mice has been characterized using imaging and physiologic approaches. Volumetric MRI assessment in the obese New Zealand mouse demonstrated a phenotype of increased visceral fat, neck fat, and increased volume of the tongue, soft palate, and lateral pharyngeal walls compared to lean mice (Brennick et al, 2009). Additionally, leptin-deficient ob/ob mice have defects in upper airway neuromechanical control which is reversed with leptin administration (Polotsky et al, 2012), which suggests that leptin protects against upper airway obstruction in obese mice, and that mice deficient in leptin may be vulnerable to the development of obstructive apnea.…”
Section: Rodents As Natural Models Of Sleep Apneamentioning
confidence: 99%
“…Since obesity is a major risk factor for obstructive sleep apnea, the upper airway of obese mice has been characterized using imaging and physiologic approaches. Volumetric MRI assessment in the obese New Zealand mouse demonstrated a phenotype of increased visceral fat, neck fat, and increased volume of the tongue, soft palate, and lateral pharyngeal walls compared to lean mice (Brennick et al, 2009). Additionally, leptin-deficient ob/ob mice have defects in upper airway neuromechanical control which is reversed with leptin administration (Polotsky et al, 2012), which suggests that leptin protects against upper airway obstruction in obese mice, and that mice deficient in leptin may be vulnerable to the development of obstructive apnea.…”
Section: Rodents As Natural Models Of Sleep Apneamentioning
confidence: 99%
“…The cross-sectional area of the nasal pharynx and its bend angle are important parameters that will affect particle deposition in this area. Limited quantitative data is available for the pharyngeal region of the New Zealand white mouse (Brennick et al, 2009). These investigators found that the dynamic cross-sectional area of the pharyngeal airways of an obese mouse model is significantly smaller than the lean counterpart, which can influence particle deposition in this area and have repercussions for subsequent particle deposition in the larynx, TB, and P region.…”
Section: Et Regionmentioning
confidence: 99%
“…Among upper airway muscles that are innervated by hypoglossal motoneurons (XIImns) (Dobbins and Feldman, 1995; Altshuler et al, 1994; Saboisky et al, 2007; Fregosi and Ludlow, 2014), the genioglossus (GG) muscle is the most important dilator because its activation increases airway caliber (Remmers et al, 1978; Brennick et al, 2009). The activity of both XIImns and GG muscle is reduced during non-rapid eye movement (NREM) sleep and it is further suppressed during rapid eye movement (REM) sleep (Sauerland and Harper, 1976; Suratt et al, 1988; Horner et al, 1989; Richard and Harper, 1991; Mezzanotte et al, 1992; Katz and White, 2004; Saboisky et al, 2007; Eckert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%